Environmental Effects of BPA - Laura Canesi; Elena Fabbri (SAGE Publishing, 2015)
Research on bisphenol A (BPA) as an environmental contaminant has now major regulatory implications toward the ecosystem health, and hence it is incumbent on scientists to do their research to the highest standards possible, in order that the most appropriate decisions are made to mitigate the impacts to aquatic wildlife. However, the contribution given so far appears rather fragmented. The present overview aims to collect available information on the effects of BPA on aquatic vertebrates and invertebrates to provide a general scenario and to suggest future developments toward more comprehensive approaches useful for aquatic species protection.